Bahay ni lola Regal Films presents. - Dantes, Dingdong; Karylle; Romero, Gloria; Regal Films ([Pasig City] Regal Films Production, 2005)
Rupert and Nina are a young recently married couple who couldn't be happier. He's zomming up the corporate ladder at the ad agency where he works, while she's a glowing lady who's just given birth to a beautiful baby girl.
VCD
Dingdong Dantes, Karylle, Gloria Romero.
Keywords: Horror films; Feature films